The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4103/0974-7753.100090
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine in the treatment of trichotillomania

Abstract: Trichotillomania is as medical condition caused by the patient himself by pulling out of is own hair, resulting in a perceptible hair loss pattern that frequently is associated with other psychiatric processes. Generally has a chronic course in most patients, and a challenging therapeutical management. There are several available options for is treatment, but the clinical response is not satisfactory in many patients. Recently, N-acetylcisteine, a glutamate modulator, has shown efficacy in the treatment of tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 6 publications
0
44
0
1
Order By: Relevance
“…Grant et al [7] evaluated the efficacy of NAC from 1,200 to 2,400 mg/day in a double-blind, placebo-controlled study on 50 adult patients with trichotillomania, and they observed a significant reduction of hair pulling compared to placebo. Similarly, there are several case reports of patients with trichotillomania successfully treated with oral NAC [8-12]. The mechanism of action of NAC in the treatment of OCD is possibly due to its action on the glutamate system: glutamatergic hyperactivity leading to excitotoxicity and oxidative stress has been implicated in the pathogenesis of OCD [13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Grant et al [7] evaluated the efficacy of NAC from 1,200 to 2,400 mg/day in a double-blind, placebo-controlled study on 50 adult patients with trichotillomania, and they observed a significant reduction of hair pulling compared to placebo. Similarly, there are several case reports of patients with trichotillomania successfully treated with oral NAC [8-12]. The mechanism of action of NAC in the treatment of OCD is possibly due to its action on the glutamate system: glutamatergic hyperactivity leading to excitotoxicity and oxidative stress has been implicated in the pathogenesis of OCD [13].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Indeed, the GSH-precursor, NAC, has demonstrated preliminary efficacy in the treatment of OCD (6567) and other OCRD such as trichotillomania (6870), excoriation disorder (69, 71) and nail biting (69, 72). While others have theorized that the beneficial effects of NAC in OCRD result from its ability to modulate glutamatergic neurotransmission (68), we propose that NAC’s capacity to increase GSH synthesis may also play a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…Third, preclinical data and research in mice and in adults with intellectual disabilities show that naltrexone, an opioid antagonist, can help in reducing excessive grooming behaviors and self-injurious behaviors [12, 35]. Finally, there is significant evidence that N-acetylcysteine, which modulates glutamate, the main neurotransmitter in the fronto-striato-thalamic-cortical circuit, may have efficacy in treating trichotillomania [3642]. …”
Section: Discussionmentioning
confidence: 99%